Shortening of the telomere length during the transition period of dairy cows in relation to biological stress - Manon Dewulf; Osvaldo Bogado Pascottini; Stijn Heirbaut; Maya Meesters; Dries S. Martens; Tim S. Nawrot; Mingqi Zhang; X. P. Jing; Leen Vandaele; Veerle Fievez; Mieke Van Eetvelde; Geert Opsomer (Scientific Reports)
Abstract Telomere length (TL) is a recognized biomarker for ageing in multiple species. In dairy cattle, the transition period is considered a very stressful period. We hypothesized that TL shortens during this period. Holstein cows (n = 61) were followed during the transition period. Blood and milk samples were collected at − 7, 3, 6, 9, 21d relative to calving to determine concentrations of oxidative, energetic metabolic, and inflammatory markers. Average relative leukocyte TL was measured by a modified qPCR protocol 7d before and 21d after parturition. We confirmed TL attrition during the transition period (P = 0.02), as TL was 1.05 ± 0.229 (mean ± SD) before, and 0.97 ± 0.191 (mean ± SD) after parturition. Univariable analyses assessed associations between blood markers and TL shortening. Greater plasma oxidative parameters, including oxidized glutathione and glutathione peroxidase, were positively and negatively (respectively) associated with TL attrition. Higher blood α- and β-globulin were all positively associated, while IGF-1, albumin-globulin ratio and albumin were negatively associated with TL attrition. Greater serum amyloid A and haptoglobin were linked with greater TL shortening. This study reveals significant TL shortening during the transition period in dairy cows and identifies significant associations with oxidative stress, metabolic stress, and inflammation. While these associations are observed, no causality can be established. Our findings suggest the need for further research to explore the effects of transition-related stress on TL dynamics.